THE PROBLEM OF EVALUATING THE COMPETITIVENESS OF THE TRAVEL SECTOR AND TOURISM IN THE COUNTRIES OF THE EUROPEAN UNION - O. Gorbunova (Вестник университета)
The articles evaluates the development and role of tourism in European Union (EU). The travel and tourism competitiveness index (TTCI) as the most authoritative indicator of the current condition and attractiveness of a country’s tourism sector has been used. The four most competitive EU countries based on the above index with their weakest and strongest features have been analysed. Based on the TTCI a comparative analysis between the four countries on one hand and Bulgaria on the other hand has been conducted. As a result the main indicators that are influencing the development of tourism in Bulgaria have been pointed out.